2014
DOI: 10.3389/fonc.2014.00194
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis as the First Step toward Personalized Treatment in Renal Cell Carcinoma

Abstract: Drug resistance mechanisms in renal cell carcinoma (RCC) still remain elusive. Although most patients initially respond to targeted therapy, acquired resistance can still develop eventually. Most of the patients suffer from intrinsic (genetic) resistance as well, suggesting that there is substantial need to broaden our knowledge in the field of RCC genetics. As molecular abnormalities occur for various reasons, ranging from single nucleotide polymorphisms to large chromosomal defects, conducting whole-genome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 142 publications
0
13
0
1
Order By: Relevance
“…It has been reported that the number of patients with RCC has been increasing at a continuous and rapid rate recently [3, 4]. This tumor has become the 10th most common in men and the 14th most common in women [5]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the number of patients with RCC has been increasing at a continuous and rapid rate recently [3, 4]. This tumor has become the 10th most common in men and the 14th most common in women [5]. …”
Section: Introductionmentioning
confidence: 99%
“…These limitations notwithstanding, our study provides helpful insights into the impact of histological subtype in a large contemporary cohort of patients, using the most recent classification system of RCC. Modern genomic techniques have confirmed the genetic distinction between histological subtypes (24). A deeper understanding of genetic events and molecular pathways underlying the differences in RCC phenotypes would be highly relevant to the effective development of future targeted and individualised therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Yeni RHK alt-tiplerinin tanımlanmasındaki zorluklar affymetrix teknolojisi ve cDNA mikrodizin gibi yüksek-verimli platformlu gen-ifadelenme profil haritaları ile aşılabilir. İleri genomik çalışmalar sonucunda yeni genetik değişimler belirlenerek kuşkusuz RHK'da kişiselleştirilmiş tedaviye doğru önemli bir adım atılacaktır (20). …”
Section: Renal Hücreli Karsinomun Moleküler Patogeneziunclassified